Cardiac disease in pregnancy. Issue 643 (May 1979) - Petch, M. C.
Abstract : The problems encountered in the management of pregnant patients with valvular, congenital and ischaemic heart disease are described with the help of illustrative cases. The increased incidence of cardiac dysrhythmias in pregnancy is also discussed.